Electronic token system using RF technology - Thamayanthi, Thangavelu (2008)
In recent years, both wired and wireless communications have been developed. Various types of wireless communication devices have been introduced in the market such as Zigbee, Bluetooth, infrared and EnOcean. From short distance wireless communication devices to long distance communication devices are being widely used in electronic field today. In wired communication devices, the usage of Universal Serial Bus (USB) has overcome the usage of serial ports. This project is concerned with the implementation of frequency modulation (FM) wireless communication in electronic token. Radio frequency (RF) technology particularly is being used for its minimum circuit complexity and low cost. It takes designing and building the electronic token and interface with the personal computer (PC) through USB. USB is used because there is lesser usage of serial ports nowadays especially in lap tops. Most of the electronic devices use USB because its application is universal. A graphical user interface (GUI) is developed for control and display purposes. This project has proved a success in building an effective token system using low cost wireless communication device.